An econometric model of the profitability: CMAC Arequipa Case. 2002-2016 - Bazán Díaz, Edwin Alberto (2020)
The present research work aims to know the impact of variables: direct credits, the inflation rate and the annual variation of real PBI expressed as a dummy variable, on profitability (ROA y ROE) of the CMAC: Arequipa during the period 2002-2016. For this inconvenient, we will get the statistic information from secondary sources. Globally, both models are significant; but, the Durbin-Watson of the ROA is highest as regards the of the ROE approaching the value of 2. By applying the econometric model with a lag in terms of specific determinants of the CMAC Arequipa profitability; return on assets (ROA) and return on heritage (ROE), direct credits are significant and at the same time have a negative effect on profitability for both. JEL: B30, C30, G21.